Training and injuries among world elite junior badminton players - Identifying the problems - Kaldau, N. C.; Kerr, S.; McCaig, S.; Hölmich, P. (Asia-Pacific Journal of Sports Medicine, Arthroscopy, Rehabilitation and Technology, 2021)
Background: The game of badminton has evolved since the early injury epidemiology studies. Since there is no published literature on injuries in elite junior badminton players from an international cohort, this study provides an updated reference of injuries in this population to inform future injury prevention strategies. The objective of this study was to report injury prevalence and training hours in elite junior badminton players participating at the World Junior Championships in 2018. Methods: A questionnaire was used to collect data and was available in English, French, Spanish, Korean, Japanese or Chinese. It was designed to collect information including basic demographics, hours of training and competition, number of tournaments per year, current and previous injuries characterized by anatomical region, diagnosis, treatment and injury duration. The questions were focused on previous significant injuries lasting a minimum of 30 days and current musculoskeletal symptoms. Results: One hundred and sixty-four of 436 players with a mean age of 17.1 years (SD ± 0.8) filled in the questionnaire. Participants represented North and South America, Europe, Asia, Africa and The Pacific's including the top 10 performing nations, providing a good overall representation of tournament participants. A total of 104 significant injuries (median duration of 90 days) with disruption of full training or competition capacity were reported. Seventy-eight (48%) players reported one or more significant injury. The most common location of significant injury was in the knee, ankle and lower back. Eleven injuries were reported as stress fractures. In 35 cases a player felt lasting limitation from a significant injury and in 37 cases a player felt lasting pain. Conclusion: Previously in their career almost 50% of the players had sustained a significant injury with a median duration of 90 days. The lower extremities and the lower back were the predominant injured regions. In one third of the injuries a player had lasting limitations or pain. Stress fractures may be a serious underestimated problem in badminton.